“THE BOOK OF WHISPERS” BY VARUJAN VOSGANIAN AS A LITERARY WAY OF UNDERSTANDING ARMENIAN GENOCIDE - PILCHIN, Department of World; Comparative Literature, Moldova State University, Chișinău, Ivan (BIBLIOPOLIS, 2020)
The well-known novel “The Book of Whispers” (2009) by Varujan Vosganian is a relevant example of how different cultures, religions and traditions interact in different historical and geographical contexts. The presentation will refer to the way of combining in the novel the historical reality and literary fiction in order to highlight the tragic faith of the Armenian people in its interaction with the neighbor nations during the 20th century. The novel will be analyzed from the perspective of the intercultural theory and culture memory concepts and is attached to the 100 years anniversary of the Armenian Genocide. A particular point in the presentation will represent my own experience of translation of the novel in Russian language.